RISK MANAGEMENT OF ROAD CONSTRUCTION - SUKMANІUK Victoriіа (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The development of the road network plays a key role in the social, economic and environmental development of a country, region cities. A key aspect for achieving the set goals and ensuring the sustainability and efficiency of road construction projects is the management of risks that arise during project planning and execution. The purpose of the work is the research and classification of risks that arise during the implementation of road construction projects, the formation of a risk management system and the search for ways to minimize their negative consequences. The paper proposes a road construction risk management mechanism, the main purpose of which is to ensure the successful implementation of the road construction project, taking into account all possible risks that may affect the process of its implementation and results. The classification of road construction risks by origin, nature, stages of the project, impact on participants, scale, which will ensure the identification of potential risks, the probability of their occurrence and the establishment of the scale of consequences from their impact, is considered. The successful implementation of road construction projects is ensured by measures to minimize the negative consequences of the impact of risks. The authors identified the main areas of risk minimization during road construction, including detailed planning, risk analysis, use of technologies and innovations, reserve time planning, quality control, stakeholder participation, insurance, environmental management, creation of reserve funds, contingency scenario or plans. A contingency scenario of risk minimization in road construction is proposed, which makes it possible to define measures and strategies for the active management of risks that may arise during a road construction project. A contingency scenario allows you to prepare for unforeseen circumstances and negative events that may occur during the implementation of a road construction project. The application of this scenario is absolutely necessary in cases where there is a high probability of the occurrence of specific risks or when these risks can have a serious impact on the project